2014
DOI: 10.1002/bmc.3254
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of cinnamaldehyde and its metabolite in rat tissues by gas chromatography–mass spectrometry

Abstract: Cinnamaldehyde (CA), an active ingredient isolated from the traditional Chinese medicine Cortex Cinnamomi, has a wide range of bioactivities. To clarify the distribution characteristics of CA, a selective and sensitive method utilizing gas chromatography-mass spetrometry was initially developed for simultaneously determining the concentration of CA and its metabolite cinnamyl alcohol in rat tissues. Selected ion masses of m/z 131, 105 and 92 were chosen, and separation of the analytes was performed on a DB-5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Moreover, Zhao et al. (2015) found that the cinnamaldehyde could be metabolized in the liver and its concentration in the liver was higher than that in the brain. As for CA, Dong et al.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Zhao et al. (2015) found that the cinnamaldehyde could be metabolized in the liver and its concentration in the liver was higher than that in the brain. As for CA, Dong et al.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the new formulation with the former drug, improved concentration was found in kidney, liver, spleen, and brain in the SME group. 29 Significant accumulation of CA was detected in the liver and kidney, with the concentration increasing to 334 ± 60.1 and 459 ± 148 ng/g, respectively. This is mainly caused by the dramatic increase in the blood that needed to be metabolized and excreted.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 97%
“…Cinnamon is obtained from the inner bark of several tree species from the genus Cinnamomum . Cinnamaldehyde (CA) is a major component of cinnamon [ 29 ]. CA possesses diverse beneficial effects, including anti-bacterial [ 30 ], anti-inflammatory [ 31 ], anti-oxidative [ 32 ], and anti-apoptotic effects [ 33 ].…”
Section: Introductionmentioning
confidence: 99%